Novel microsatellite loci for Sebaea aurea (Gentianaceae) and cross-amplification in related species(1) - Kissling, Jonathan (Botanical Society of America, 2013)
• Premise of the study: Microsatellite loci were developed in Sebaea aurea (Gentianaceae) to investigate the functional role of diplostigmaty (i.e., the presence of additional stigmas along the style). • Methods and Results: One hundred seventy-four and 180 microsatellite loci were isolated through 454 shotgun sequencing of genomic and microsatellite-enriched DNA libraries, respectively. Sixteen polymorphic microsatellite loci were characterized, and 12 of them were selected to genotype individuals from two populations. Microsatellite amplification was conducted in two multiplex groups, each containing six microsatellite loci. Cross-species amplification was tested in seven other species of Sebaea. The 12 novel microsatellite loci amplified only in the two most closely related species to S. aurea (i.e., S. ambigua and S. minutiflora) and were also polymorphic in these two species. • Conclusions: These results demonstrate the usefulness of this set of newly developed microsatellite loci to investigate the mating system and population genetic structure in S. aurea and related species.